Surgical management of recurrent urethrovaginal fistula with a skin island flap - Martan, Alois; Svabik, Kamil; Zamecnik, Libor; Masata, Jaromir (International urogynecology journal, 2019)
INTRODUCTION AND HYPOTHESIS: A urethrovaginal fistula is a possible rare complication of tension-free vaginal tape procedures. Surgical management of these fistulas is sometimes complicated, and failure can occur. The operation is difficult when the defect between the urethra and the vagina is larger or scarred, so surgical intervention and the preferred technique are controversial. METHODS: The patient was referred to our department, where the first operation was performed to address the urethrovaginal fistula by the transvaginal and transabdominal approach with interposed omentum. This initial repair failed, resulting in a large urethrovaginal fistula with minimal redundant anterior vaginal wall to provide a tension-free closure. This video presentation describes the second operation-transvaginal repair of a large recurrent urethrovaginal fistula using the skin island flap technique. RESULTS: The video of the procedure shows how to address a recurrent urethrovaginal fistula by employing a skin flap. An examination during the patient's follow-up visit 3 months later revealed excellent healing and persistent stress urinary incontinence (SUI). Six months after the fistula repair, the patient underwent a bulking agent procedure. CONCLUSIONS: The skin island flap procedure allowed the larger defect to heal, though it did not address the SUI, which was later treated by application of a bulking agent.
Keywords: recidiva; Humans; Native tissue repair; suburetrální pásky; Female; Aged; Urethrovaginal fistula; senioři; lidé; vaginální píštěl; Plastic Surgery Procedures; Suburethral Slings; Urinary Incontinence, Stress; stresová inkontinence moči; ženské pohlaví; zákroky plastické chirurgie; Vaginal Fistula; Urinary Fistula; Recurrence; Skin flap; močové píštěle